TRANSLATION OF PHRAZEOLOGICAL UNITS FROM ENGLISH INTO UZBEK LANGUAGE (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article examines the importance of linguistic and semantic features of phraseological units in the process of translation. In addition, the correct use of English phraseological units in the Uzbek context and the problems faced by translators are analyzed.